If you repeat the perpendicular line segment construction twice using paper folding, you can construct:

A.the midpoint of a line segment.
B.an angle congruent to a given angle.
C.a parallel to a line through a point not on the line.
D.an angle bisector.

Answers

Answer 1

Final answer:

By repeating the perpendicular line segment construction twice using paper folding, one can effectively find the midpoint of a line segment, demonstrating the application of geometric principles and theorems related to perpendicular constructions.

Explanation:

If you repeat the perpendicular line segment construction twice using paper folding, you can construct the midpoint of a line segment. This is based on the principle that constructing perpendiculars at the ends of a given line segment and then erecting a third perpendicular midway between them will intercept the line segment at its midpoint. This is affirmed by the theorems that explain the geometrical properties and relationships of constructing perpendicular lines and their midpoints.

To elucidate, let's take a line segment AB of a certain length, and fold the paper to construct a perpendicular line at point A. Next, repeat the same action at point B. Now, fold the paper to find the midpoint of AB, and erect a perpendicular line at this midpoint. This results in the third perpendicular intersecting AB exactly at its midpoint, demonstrating that this method is effective for finding the midpoint of a line segment, thereby validating option A.

Answer 2

You can construct: The midpoint of a line segment.

The correct option is (A).

Paper folding constructions can be used to create geometric shapes and lines based on certain properties. Let's break down each of the given options and see if they can be achieved by repeating the perpendicular line segment construction twice:

A. The midpoint of a line segment: Yes, this can be achieved. Folding a line segment in half will give you its midpoint. By repeating the perpendicular line segment construction twice, you fold the line segment once to find a point equidistant from both endpoints (which is the midpoint), and folding it again should confirm that the resulting point is indeed the midpoint.

B. An angle congruent to a given angle: No, this cannot be achieved. The perpendicular line segment construction does not involve creating or manipulating angles, so it cannot be used to construct an angle congruent to a given angle.

C. A parallel to a line through a point not on the line: No, this cannot be achieved. The perpendicular line segment construction does not involve creating parallel lines.

D. An angle bisector: No, this cannot be achieved. Again, the perpendicular line segment construction does not involve manipulating angles, so it cannot be used to construct an angle bisector.

Therefore, the correct option is:

A. The midpoint of a line segment.


Related Questions

Consider the following equation

Select the equation that has the same solution as the given equation.

Answers

Answer:

Option C [tex](3/2)p-5+(9/4)p=7-(5/4)p[/tex]

Step-by-step explanation:

we have that

The given equation is

[tex]-16p+37=49-21p[/tex]

Solve for p

Group terms that contain the same variable

[tex]-16p+21p=49-37[/tex]

Combine like terms

[tex]5p=12[/tex]

[tex]p=12/5[/tex]

[tex]p=2.4[/tex]

we know that

If a equation has the same solution as the given equation, then the solution of the given equation must satisfy the equation

Verify each case

case A) we have

[tex]2+1.25p=-3.75p+10[/tex]

substitute the value of p=2.4 in the equation and then compare the results

[tex]2+1.25(2.4)=-3.75(2.4)+10[/tex]

[tex]5=1[/tex] ----> is not true

therefore

The equation does not have the same solution as the given equation

case B) we have

[tex]-55+12p=5p+16[/tex]

substitute the value of p=2.4 in the equation and then compare the results

[tex]-55+12(2.4)=5(2.4)+16[/tex]

[tex]-26.2=28[/tex] ----> is not true

therefore

The equation does not have the same solution as the given equation

case C) we have

[tex](3/2)p-5+(9/4)p=7-(5/4)p[/tex]

substitute the value of p=2.4 in the equation and then compare the results

[tex](3/2)(2.4)-5+(9/4)(2.4)=7-(5/4)(2.4)[/tex]

[tex]4=4[/tex] ----> is true

therefore

The equation has the same solution as the given equation

case D) we have

[tex]-14+6p=-9-6p[/tex]

substitute the value of p=2.4 in the equation and then compare the results

[tex]-14+6(2.4)=-9-6(2.4)[/tex]

[tex]0.4=-5.4[/tex] ----> is not true

therefore

The equation does not have the same solution as the given equation

write y+1=-2x-3 in standard form​

Answers

Answer:

2y=-5x

Step-by-step explanation:

First you mark your terms, which means to basically put the equation in order.

Then you add, for instance, first you'll add y and 1, you'll have 2y because y means one. Then, you'll have -2 minus 3 and you'll get -5 then you carry on the variables to the solutions.

Answer:

2y=-5x

hope this helps :3

What is the volume of the pyramid?
A solid right pyramid has a square base. The length of the
base edge is 4 cm and the height of the pyramid is 3 cm.

Answers

Answer: 16 cm^2.

Step-by-step explanation: The volume of a pyramid is equal to one-third the product of the area of the base and the height:

[tex]V=\frac{1}{3}A*h[/tex]

In this case, the base is a square, so its area is:

A=L^2 where "L" is the lenght of the base edge

So the volume would be:

[tex]V=\frac{1}{3}L^{2} *h[/tex]

[tex]V=\frac{1}{3}4^{2} *3[/tex]

V=16*3/3

[tex]V=16cm^{2}[/tex]

Help me out again Please

Answers

1= 25
2= 50
3= 25x3 = 75

Or you can do 1/25 = 3/x
X= 75

100/25 = 4


25x 12 = 300
If this is confusing. Write the answers on the following


First box is 75
Second box is 4
Third box is 300

Hope this helps!

Given: -x > 4. Choose the solution set.

Answers

Final answer:

The solution to the inequality -x > 4 is all real numbers less than -4, which can be expressed as the interval (-∞, -4). This is found by dividing both sides by -1 and reversing the inequality to x < -4.

Explanation:

When considering the inequality -x > 4, we are trying to find the set of all values for the variable x that make the inequality true. The solution to such an inequality requires inverse operations and understanding the rules for inequalities, especially the rule that multiplying or dividing both sides of an inequality by a negative number reverses the inequality symbol.

Step by step, let's solve the given inequality:

Divide both sides of the inequality by -1 to isolate x. It is important to remember that dividing or multiplying both sides of an inequality by a negative number reverses the inequality, so our inequality becomes x < -4 after this step.Now that we have x isolated, we can interpret the solution set. The values of x that satisfy this inequality are all real numbers less than -4. Therefore, the solution set can be written in interval notation as (-∞, -4).

This means that any number lower than -4 will be a valid solution for the inequality -x > 4. It's also valuable to visualize this set on a number line, where everything to the left of -4 (but not including -4 itself) is part of the solution set.

what is the distance between (1,4) and (4,0) ?

Answers

Answer:

5 units

Step-by-step explanation:

To calculate the distance (d) use the distance formula

d = √ (x₂ - x₁ )² + (y₂ - y₁ )²

with (x₁, y₁ ) = (1, 4) and (x₂, y₂ ) = (4, 0)

d = [tex]\sqrt{(4-1)^2+(0-4)^2}[/tex]

   = [tex]\sqrt{3^2+(-4)^2}[/tex]

   = [tex]\sqrt{9+16}[/tex] = [tex]\sqrt{25}[/tex] = 5

Question 1
The number of laptop computers sold each month for one year was
recorded by an electronics store. The results were 14, 15, 15, 30, 29, 5, 9, 15,
21, 21, 26, and 15. Calculate the median number of laptop computers sold
per month.​

Answers

Final answer:

The median number of laptop computers sold per month is 15, calculated by arranging the sales data in ascending order and averaging the two middle values in the even-numbered dataset.

Explanation:

The median of laptop computers sold per month can be calculated by first arranging the given numbers in ascending order and then finding the middle value. If there is an even number of observations, the median is the average of the two middle numbers.

Arrange the sales numbers in ascending order: 5, 9, 14, 15, 15, 15, 15, 21, 21, 26, 29, 30.Since there are 12 months, we have an even number of observations, so we take the average of the 6th and 7th values which are both 15.The median number of laptop computers sold per month is 15.

What is the slope of the line shown in the graph?
A) 3/2
B) 2/3
C) -3/4
D) -2/3

Answers

Choose two points

(4,1) and (-3 , 5)

rise/run = 4/6

Simplify - 2/3

Answer = B) 2/3

Hope this helps!!

we can simply get the slope by using two points off the line, hmmmm say the line passes through (0,3) and (-3,5)

[tex]\bf (\stackrel{x_1}{0}~,~\stackrel{y_1}{3})\qquad (\stackrel{x_2}{-3}~,~\stackrel{y_2}{5}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{5-3}{-3-0}\implies \cfrac{2}{-3}\implies -\cfrac{2}{3}[/tex]

Which is a solution to the equation?
(х-2)(х + 5) = 18?

Answers

[tex]\bf (x-2)(x+5)=18\implies \stackrel{\mathbb{F~O~I~L}}{x^2+3x-10}=18\implies x^2+3x-28=0 \\\\\\ (x-4)(x+7)=0\implies x= \begin{cases} 4\\ -7 \end{cases}[/tex]

1 and 3/4 + 2 and 3/8

Answers

Hello There!

1[tex]\frac{3}{4}[/tex] + 2[tex]\frac{3}{8}[/tex] = 4[tex]\frac{1}{8}[/tex]

First, when we are trying to find the sum of a mixed number, I always add the natural numbers first meaning that the numbers before the fraction so I would add 1 and 2 together so we get a sum of 3 and now we are left with just a plain fraction.

Next, I find the least common denominator which is the smallest number that can be a common denominator for a set of fractions. Our lowest common denominator is 8 because [tex]\frac{3}{4}[/tex] = [tex]\frac{6}{8}[/tex].

Then, we add our fractions with the denominator of 8 together and get a sum of 9/8 which we can turn into a mixed number because the numerator is bigger than our denominator.

Our mixed number turns into 1 and 1/8 and we add 4 to it because that was the sum of our natural numbers and get a sum of 4 and 1/8

ANSWER 4 1/8

A change machine can accept $1, $5, $10, and $20 bills and returns quarters. What is the domain and range of this situation?

Answers

Answer:

Domain {1,5,10,20}

Ranger {4,20,40,80}

Step-by-step explanation:

$1=4 quarters

$5=20 quarters

$10=40 quarters

$20=80 quarters

Domain {1,5,10,20}

Ranger {4,20,40,80}

Simplify the expression 3/2 (5/3) -1 1/4 + 1/2

Answers

Answer:

7/4, 1.25 or 1 3/4

Step-by-step explanation:

Answer:

Exact form  7/4

Decimal form 1.75

Mixed Number 1 3/4

Step-by-step explanation:

The roots of the equation 2×^2 + 3x -4=0 are a and b.
find the values of

a^2ß^2​

Answers

Answer:

hello : a²b² =4

Step-by-step explanation:

2ײ + 3x - 4=0

The roots of this equation exist because (2)(-4)<0

note : a'x²+b'x +c' =0.......The roots of this equation : a and b

a×b = c'/a'       a' =2 and b'=3 and c' = - 4

in this exercice ; a²b² = (ab)² = (c'/a')²  = (-4/2)² = (-2)² =4

Answer:

4

Step-by-step explanation:

given a quadratic equation in standard form

y = ax² + bx + c = 0 : a ≠ 0

with roots α and β, then

the sum of the roots α + β = - [tex]\frac{b}{a}[/tex] and

the product of the roots αβ = [tex]\frac{c}{a}[/tex]

2x² + 3x - 4 = 0 ← is in standard form

with a = 2, b = 3 and c = - 4

αβ = [tex]\frac{-4}{2}[/tex] = - 2, hence

α²β² = (αβ)² = (- 2)² = 4

I NEED HELP NOW!!!! I'LL MARK YOU BRAINLIEST IF YOU ANSWER!!!!!

Answers

Answer:

0, 5, 7, 11, ...

Step-by-step explanation:

1^2 = 1; 1 - 1 = 0; 0 is divisible by 6

5^2 = 25; 25 - 1 = 24; 24 is divisible by 6

7^2 = 49; 49 - 1 = 48; 48 is divisible by 6

11^2 = 121; 121 - 1 = 120; 120 is divisible by 6

find the length of AB leave your answer in terms of pi help please ​

Answers

[tex]\bf \textit{arc's length}\\\\ s=\cfrac{\pi \theta r}{180}~~ \begin{cases} r=radius\\ \theta =\textit{angle in}\\ \qquad \textit{degrees}\\ \cline{1-1} r=6\\ \theta =30 \end{cases}\implies s=\cfrac{\pi (30)(6)}{180}\implies s=\pi[/tex]

The first two steps in determining the solution set of the system of equations, y = x2 - 2x - 3 and y = -x +3, algebraically are
shown in the table.
Step
Equation
Step 1 XP-2x-3--x+3
Step 2
0=x2-X-6
Which represents the solution(s) of this system of equations?
(3.0) and (-2,5)
(-6, 9) and (1, 2)
(-3,6) and (2, 1)
(6.-3) and (-1.4)

Answers

Answer:

(3,0) and (-2,5)

Step-by-step explanation:

The solutions of the equations are A ( 3 , 0 ) and B ( -2 , 5 ) and the graph is plotted

What is an Equation?

Equations are mathematical statements with two algebraic expressions flanking the equals (=) sign on either side.

It demonstrates the equality of the relationship between the expressions printed on the left and right sides.

Coefficients, variables, operators, constants, terms, expressions, and the equal to sign are some of the components of an equation. The "=" sign and terms on both sides must always be present when writing an equation.

Given data ,

Let the equation be represented as C

Now , the value of C is

Substituting the values in the equation , we get

y = x² - 2x - 3   be equation (1)

y = -x + 3   be equation (2)

On simplifying , we get

-x + 3 = x² - 2x - 3

Adding x on both sides , we get

x² - 3 - x = 3

Subtracting 3 on both sides , we get

x² - x - 6 = 0

On factorizing , we get

( x - 3 ) ( x + 2 ) = 0

So , the two values of x are 3 and -2

Hence , the solutions of equations are A ( 3 , 0 ) and B ( -2 , 5 )

To learn more about equations click :

https://brainly.com/question/19297665

#SPJ7

the sum of three consecutive natural numbers is 156 find the number which is the multiple of 13 out of these numbers​

Answers

Answer:

52 is the multiple of 13

Step-by-step explanation:

3x+3=156

3x=153

x=52

Answer:

52 is the multiple of 13 out of 51 , 52, 53 numbers​.

Step-by-step explanation:

Given:  Sum of three consecutive integers 156

To find: Three consecutive integers .

Solution: We have given that

Let first consecutive number  x ,

Second consecutive number=   x+1

Third number =  x+2

According to question :

Sum of three consecutive number

x + x+1 +x+2 = 156 .

Combine like term

3x+3 = 156

On subtracting by 3 both side

3x + 3 -3 = 156 - 3

3x = 153

On dividing by 3

x = 51.

X+1 = 51+1

x+1 = 52.

x +3 = 51+2 = 53.

We can see second number 52 is multiple of 13.

Therefore, 52 is the multiple of 13 out of 51 , 52, 53 numbers​.

(4x^2y^3+2xy^2-2y)-(-7x^2y^3+6xy^2-2y)

Answers

Answer:

x y^2 (11 x y - 4)

Step-by-step explanation:

Simplify the following:

4 x^2 y^3 + 2 x y^2 - 2 y - (-7 x^2 y^3 + 6 x y^2 - 2 y)

Factor y out of -7 x^2 y^3 + 6 x y^2 - 2 y:

4 x^2 y^3 + 2 x y^2 - 2 y - y (-7 x^2 y^2 + 6 x y - 2)

-y (-2 + 6 x y - 7 x^2 y^2) = 2 y - 6 x y^2 + 7 x^2 y^3:

4 x^2 y^3 + 2 x y^2 - 2 y + 2 y - 6 x y^2 + 7 x^2 y^3

Grouping like terms, 4 x^2 y^3 + 2 x y^2 - 2 y + 2 y - 6 x y^2 + 7 x^2 y^3 = (4 x^2 y^3 + 7 x^2 y^3) + (2 x y^2 - 6 x y^2) + (2 y - 2 y):

(4 x^2 y^3 + 7 x^2 y^3) + (2 x y^2 - 6 x y^2) + (2 y - 2 y)

x^2 y^3 4 + x^2 y^3 7 = 11 x^2 y^3:

11 x^2 y^3 + (2 x y^2 - 6 x y^2) + (2 y - 2 y)

x y^2 2 + x y^2 (-6) = -4 x y^2:

11 x^2 y^3 + -4 x y^2 + (2 y - 2 y)

2 y - 2 y = 0:

11 x^2 y^3 - 4 x y^2

Factor x y^2 out of 11 x^2 y^3 - 4 x y^2:

Answer:  x y^2 (11 x y - 4)

Answer:  xy2 • (11xy - 4)

Step-by-step explanation:

4 x^2 y^3 + 2 x y^2 - 2 y - (-7 x^2 y^3 + 6 x y^2 - 2 y)

Factor y out of -7 x^2 y^3 + 6 x y^2 - 2 y:

4 x^2 y^3 + 2 x y^2 - 2 y - y (-7 x^2 y^2 + 6 x y - 2)

-y (-2 + 6 x y - 7 x^2 y^2) = 2 y - 6 x y^2 + 7 x^2 y^3:

4 x^2 y^3 + 2 x y^2 - 2 y + 2 y - 6 x y^2 + 7 x^2 y^3

Grouping like terms, 4 x^2 y^3 + 2 x y^2 - 2 y + 2 y - 6 x y^2 + 7 x^2 y^3 = (4 x^2 y^3 + 7 x^2 y^3) + (2 x y^2 - 6 x y^2) + (2 y - 2 y):

(4 x^2 y^3 + 7 x^2 y^3) + (2 x y^2 - 6 x y^2) + (2 y - 2 y)

x^2 y^3 4 + x^2 y^3 7 = 11 x^2 y^3:

11 x^2 y^3 + (2 x y^2 - 6 x y^2) + (2 y - 2 y)

x y^2 2 + x y^2 (-6) = -4 x y^2:

11 x^2 y^3 + -4 x y^2 + (2 y - 2 y)

2 y - 2 y = 0:

11 x^2 y^3 - 4 x y^2

Factor x y^2 out of 11 x^2 y^3 - 4 x y^2:

Answer:  x y^2 (11 x y - 4)

If f(x) = 3x + 10 and g(x) = 2x– 4, find (f+ g)(x).

Answers

Answer:

5x+6

Step-by-step explanation:

f(x) = 3x + 10

g(x) = 2x– 4

(f+ g)(x) = 3x+10 + 2x-4

Combine like terms

           = 5x+6

Answer:

5x + 6

Step-by-step explanation:

 (f+ g)(x) = 3x + 10 +  2x– 4

               = 5x + 6

Interest rate is 4.25%, the time is 3 1/4 years, simple interest is $330. What is the principal?

Answers

Answer:

$2389.14

Step-by-step explanation:

The equation is I = PRT

330= (0.0425)(3.25)P

P=2389.14

Answer:

$2389.14.

Step-by-step explanation:

Use the formula

I =  PRT/100 where I = interest , P  is the principle, t = time and R = the rate.

330 = P * 4.25 * 3.25 / 100

33000 = P * 13.8125

P = 33,000 / 13.8125

P = $2389.14.

a pair of shoes is on sale for 30% off . the original price is p. which expression can be used to find the price of shoes after the dicount?​

Answers

Answer:

.30p

Step-by-step explanation:

4x(3x-7)-19x^2 simplify the expression below

Answers

Answer:

opening the bracket, the expression becomes

12x^2-28-19x^2

collect like terms

12x2-19x^2-28

-7x^2-28

-7(x^2+4)

What are the x- and y-intercepts for the equation "2x + 3y = 6"?
(2,0) & (3,0)
(0, 2) & (3, 0)
(0,3) & (2,0)
(0,3) & (0,2)​

Answers

Answer:

(0,2) & (3,0)

Step-by-step explanation:

Given the equation [tex]2x+3y=6[/tex]:

Step 1:

To find the y-intercept, you want to set the x value to zero. This will allow you to solve for y, and find where the equation intercepts why on the 0 line:

[tex]2(0)+3y=6 \\ 0+3y=6\\ 3y=6\\ y=\frac{6}{3} \\  y = 2[/tex]

So, at x=0, y=2. or (0,2)

Step 2:

Set y = 0 and solve for x:

[tex]2x+3(0)=6\\ 2x+0=6\\ 2x=6\\ x=\frac{6}{2}\\  x=3[/tex]

so at y=0, x=3. which is the same as saying: when x=3, y=0, or (3,0)

2x+3y=6
The answer is
(0,2) & (3,0)
You have to put 0 in the x then solve for y
After u get y replace the number in y and solve for x

What is the volume of a rectangle Kay prism that is 16 meters by 25 meters by 37 meters? PLZ HELP QUICK

Answers

To find the volume multiply the three dimensions:

16 x 25 x 37 = 14,800 cubic meters.

The values in the table represent an exponential function. What is the common ratio of the associated geometric sequence?

Answers

Answer:

D. 3

Step-by-step explanation:

[tex]a_1,\ a_2,\ a_3,\ ...,\ a_n-\text{geometric series}\\\\r=\dfrac{a_2}{a_1}=\dfrac{a_3}{a_2}=\dfrac{a_4}{a_3}=...=\dfrac{a_n}{a_{n-1}}-\text{common ratio}\\\\\text{From the table we have:}\\\\a_1=7,\ a_2=21,\ a_3=63,\ a_4=189,\ a_5=567\\\\\text{Check the common ratio:}\\\\\dfrac{21}{7}=3\\\\\dfrac{63}{21}=3\\\\\dfrac{189}{63}=3\\\\\dfrac{567}{189}=3\\\\\bold{CORRECT}[/tex]

Hamid ha gained weight, he now weighs 88kg which is 10% higher than the normal, what i Hamid normal weight?

Answers

Answer:

80 kg is Hamid's normal weight

Step-by-step explanation:

The following equation will help you to find the answer:

(1.10)x = 88

Answer:79.2kg

Step-by-step explanation:

10%of 88kg is 8.8. Subtract 8.8 from 88 and the answer is 79.2.

What is the value of x?
50°
100
А. 50°
Ов. 150°
Ос. 100°
Op. 30°

Answers

Answer:

The answer is 30

Step-by-step explanation:

BC the inside of a triangle equals 180

The answer is 30 to this question because 100+50 is 150 and then 30+1250 is 180 and 180 is a perfect triangle

6 x j = 42 ??????? Help

Answers

Answer:

j = 7

Step-by-step explanation:

flip the equation around: instead of using multiplication you use division to find out what j is.

1st step: 42 divided by 6 is 7

2nd step: (check your answer): 7 times 6 does equal 42, therefore j = 7 is correct.

Answer:

[tex]\huge \boxed{J=7}[/tex]

Step-by-step explanation:

Switch sides.

[tex]\displaystyle6j=42[/tex]

Divide by 6 from both sides.

[tex]\displaystyle \frac{6j}{6}=\frac{42}{6}[/tex]

Simplify, to find the answer.

[tex]\displaystyle 42\div6=7[/tex]

[tex]\huge \boxed{j=7}[/tex], which is our answer.

At a point on the ground 60 Ft
from the base of a tree, the distance
to the top of the tree is 4 ft more
than 2 times the height of the tree.
Find the height of the tree in ft.​

Answers

The height of the tree is 32 feet.

Step-by-step explanation:

Let the height of the tree be x.

Connect the top of the tree, the point on the ground, and the bottom of the tree to form a right triangle.

Use Pythagorean theorem to solve for x.

(4+2x)^2 = x^2 + 60^2

x = 32

Final answer:

The height of the tree is 4 feet.

Explanation:

To find the height of the tree, we can set up a right triangle with the tree height as one leg, the distance from the base of the tree as the other leg, and the distance to the top of the tree as the hypotenuse. Let's call the tree height x. From the given information, we can write the equation:

x = 2x + 4

Simplifying this equation, we get:

x = 4

Therefore, the height of the tree is 4 feet.

Learn more about Geometry here:

https://brainly.com/question/31408211

#SPJ3

How do you do this question down below?

Answers

Answer:

y = 3m - 6

Step-by-step explanation:

y = mx + b

b is the point where the line cuts the y axis.

That happens at (0,-6)

So far what you have on this equation is

y = mx - 6

You could use the point that cuts the x axis to find m.

y = 0

x = 2

0 = m*2 - 6                  Add 6 to both sides

6 = m*2 - 6 + 6

6 = 2*m                        Divide by 2

6/2 = 2m/2                   Do the division

3 = m

Answer

y = 3m - 6

Other Questions
Wich of following is(are) the solution(s) to |x+3| = 12Answer: x=9 nanotechnology is unique, because it is (blank) enough to show quantum mechanical features but still large enough to be controlled and manipulated. How much heat is released when you condense 93.9 g of water vapor? Show work please Lakota is buying a new laptop. He wants to use google as his main search engine. He should be sure which internet browser(s) are loaded on his computer? Match the plant with the country of origin.Southwest Asia1. maizeEthiopia2. tomatoAfrica3. coffeeMexico4. wheatNorth America5. banana How did Theodore Roosevelt become a party nominee in the presidential election of 1912? Roosevelt split from the Republicans and formed the Progressive Party. Roosevelt split from the Republicans and joined the Democratic Party. Roosevelt split from the Democrats and formed a new Republican party. Roosevelt split from the Democrats and formed the Populist Party. Durind the summer, Ms. Stevenson likes to swim. Her goal next summer is to swim1,456 laps. If she swims 28 laps a day, how many days will it take Ms. Stevenson to reach her goal? How is preparation related to the production of a Greek play? Which nation helped most to bail out Greeces failing economy? Please help me now please Which of the following is the general term for the sequence a, -a, a, -a, . . . ? What is the solution to the system of equations below? y = 3/4 x - 12 and y = 4x - 31(4, 15)(4, 12)(4, 9)(4, 47) The population of the planet doubled in fifty years to reach _______ in 1999?6 billion7 billion5 billion10 billion Read the sentences. The tone of the speech was stern. The speaker called for hard work and determination. Which is the best way to combine the sentences? The tone of the speech was stern . . . the speaker called for hard work and determination. The tone of the speech was stern; and the speaker called for hard work and determination. The tone of the speech was stern, the speaker called for hard work and determination. The tone of the speech was stern; the speaker called for hard work and determination. Under the rule of man __________. A. all people, including government leaders, are subject to the law B. everyone follows written laws C. rulers are often fair and just D. government authority rests in the hands of one persons decisions Michael and Tom are brothers. Their combined age is 20, and Tom is 4 years older than Michael. What are Michael and Toms ages? What are three ways plastics negatively affect oceansApex semester 2 5.1.3 Which piece of art is most similar to Marcel Duchamp's ready-made pieces? Why do you think the SAT asks you to write a critical analysis of an argumentative/analytical text for their exam? Why would an interpretation alter character depiction from a source text? Steam Workshop Downloader